Prentice Hall literature : timeless voices, timeless themes - Kinsella, Kate (Upper Saddle River, New Jersey : Pearson Prentice Hall, 2003)
Students will encounter Native American works from several of the areas. Student will gain insight into Puritan value and style as they read Anne Bradstreets.
Unit1. Beginnings-1750 -- Unit2. A Nation is Born -- Unit3. A Growing Nation (1800-1870) -- Unit4. Division, Reconciliation, and Expansion(1850-1914) -- Unit5. Disillusion, Defiance, and Discontent(1914-1946) -- Unit6. Prosperity and Protest(1946-Present)
Includes index.
Keywords: READERS (SECONDARY)